1979
DOI: 10.1128/jvi.31.3.596-607.1979
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the simian virus 40 tumor antigens in transformation of Chinese hamster lung cells: studies with simian virus 40 double mutants

Abstract: Simian virus 40 mutants containing both a tsA mutation (rendering the 90,000 molecular weight [90K] T-antigen thermolabile) and a deletion between 0.54 and 0.59 map units (reducing the size and the amount of the 20K t-antigen) were used to transform Chinese hamster lung cells. The frequencies of transformation by the double mutants were comparable to that of the tsA mutant alone by both the focus and agar assays except when the cells were serum depleted before infection. Growth-arrested cells were transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Our explanation is also consistant with the finding that rat cells infected with d154-59/tsA double mutants always generate temperature-sensitive (N-type) transformants (13). However, it has been shown that double mutant-infected Chinese hamster lung cells can give rise to both A-type and N-type transformants (7). This result raises the possibility that some cells might be able to supply the small t antigen maintenance function(s).…”
supporting
confidence: 78%
“…Our explanation is also consistant with the finding that rat cells infected with d154-59/tsA double mutants always generate temperature-sensitive (N-type) transformants (13). However, it has been shown that double mutant-infected Chinese hamster lung cells can give rise to both A-type and N-type transformants (7). This result raises the possibility that some cells might be able to supply the small t antigen maintenance function(s).…”
supporting
confidence: 78%
“…Both proteins influence viral transformation. Analysis of deletion mutants suggests that the small t antigen is required for the efficient initiation of transformation when growth is restricted soon after infection (5, 11,28,42) but plays a miniimal role in the subsequent maintenance of the transformed phenotype either in vitro or in vivo (22,38). Large T antigen, on the other hand, may play a continuingly active role in transformation.…”
mentioning
confidence: 99%
“…Transformed cells. The N-and A-type tsA209, SV40-transformed rat cells and the tsA209 and tsA209 viable deletion double-mutant-transformed Chinese hamster lung (CHL) cells have been described previously (20,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…The gels were then treated with 0.2 M NaOH-0.6 M NaCl for 45 to 60 min, neutalized with 1 M Tris-hydrochloride (pH 7.3)-0.6 M NaCl for 45 min, and equilibrated with 6x SSC (lx SSC is 0.15 M NaCl plus 0.015 M sodium citrate) for 30 to 45 min with gentle rotation. Blotting on nitroceliulose membrane filter paper (0.45 pm; type HAWP; Millipore Corp.) was performed downward (gel at the top) for approximately 3 h and upward for approximately 20 h, soaking the 3 MM paper bridge in 6x SSC. The nitrocellulose paper was rinsed for 15 min in 6x SSC and air dried.…”
Section: Methodsmentioning
confidence: 99%